The influence of original acquisition on existing rights in rem of third parties - Andorkó, Imre; Kiss, Csongor Gábor (Acta Agraria Debreceniensis, 2012)
In this lecture we will give an overview about the aspects and traditions of distinction between original and derivative getting modes.We will examine which of the getting modes can be looked at as „obviously” original and review how they affect the third party’s rights existing on property. This study makes it possible to explore the analyzed original getting modes common characteristics and to review the dogmatic and law political aspects regarding the getting modes regulations.